Oxidation state and coordination environment of Pb in U-bearing minerals. (15th November 2019) - Syverson, Drew D.; Etschmann, Barbara; Liu, Weihua; Ram, Rahul; Mei, Yuan; Lanzirotti, Tony; Mercadier, Julien; Brugger, Joël
Abstract: This study examines the oxidation and coordination of lead (Pb) in the uranium (U) minerals uraninite (UO2 ), coffinite (USiO4 ), and brannerite (UTi2 O6 ), and minerals that have U as a minor constituent, zircon (ZrSiO4 ) and titanite (CaTiSiO5 ). The characterization of Pb was conducted through a combination of micro-synchrotron X-ray fluorescence mapping (µSXRF) and micro-X-ray absorption spectroscopy (µXAS), collected at the Pb LII and LIII edge on characterized grains (electron microscopy and X-ray diffraction) from a range of geological settings and ages. For all minerals considered in this study, Pb LII and LIII X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) data indicate that Pb exists as Pb 2+ . In the case of uraninite, DFT structure optimization calculations suggest that the substitution of Pb 2+ for U 4+ is facilitated by the stereochemically active electron lone pair indicative of Pb 2+, which effectively takes the place of an oxygen vacancy (coupled substitution Pb 2+  + □ = U 4+  + O 2− ). In detail, however, the EXAFS and XANES data, supported by first principle calculations of the XANES associated with Pb 2+ replacing U 4+ in the crystal lattice of uraninite, indicate that Pb 2+ is present in a less distorted coordination than suggested by DFT, which may reflect a yet to be characterized link between interstitial oxygen defects and Pb 2+ incorporation, rather than a simple oxygen vacancy. For coffinite, the XANES data demonstrate that Pb exists mainly as Pb 2+ in the form of galena, indicating limited stability of the isomorphous substitution in coffinite. In contrast, Pb is homogeneously distributed in the metamict mineral brannerite, which displays a distinct XANES spectrum suggestive of Pb 2+ bonded to oxygens in a highly distorted coordination environment. Pb LII XANES indicate that radiogenic Pb exists predominantly as Pb 2+ within the crystal lattice of zircon and as distinct mineral PbO nano-scale inclusions or domains. Additionally, Pb LII XANES measurements also indicate that Pb 2+ exists within titanite although the coordination environment is unclear. Overall, these data suggest that the previous indications of the presence of Pb 4+ in radioactive minerals need to be reconsidered. The nature of radiogenic Pb 2+ incorporation in U-bearing minerals controls the mobilization of Pb in hydrothermal fluids and the utility of a mineral as a geochronometer. The Pb valence and coordination data presented in this study provide fundamental constraints imperative for our understanding of the controls governing the mobilization of radiogenic Pb during water-rock interaction and metamorphism.